Obesity induced by high fat diet attenuates postinfarct myocardial remodeling and dysfunction in adult B6D2F1 mice. (July 2015) - Poncelas, Marcos; Inserte, Javier; Vilardosa, Úrsula; Rodriguez-Sinovas, Antonio; Bañeras, Jordi; Simó, Rafael; Garcia-Dorado, David
Abstract: Obesity is a major risk factor for cardiovascular morbidity and mortality. However, some studies suggest that among patients with established cardiovascular disease, obesity is associated with better prognosis, a phenomenon described as the obesity paradox. In this study we tested the hypothesis that obesity with hyperinsulinemia and without hyperglycemia attenuates the impact of transient coronary occlusion on left ventricular remodeling and function. B6D2F1 mice from both genders fed with a high fat diet (HFD) or control diet for 6 months were subjected to 45 min of coronary occlusion and 28 days of reperfusion. Left ventricular dimensions and function were assessed by serial echocardiography, and infarct size was determined by Picrosirius red staining. HFD mice developed obesity with hypercholesterolemia and hyperinsulinemia in the absence of hyperglycemia or hypertension. During the period of feeding, no changes were observed in ventricular mass, volume or function, or in vascular reactivity. HFD attenuated the consequences of transient coronary occlusion as shown by a marked reduction in infarct size (51%, P = 0.021) and cardiac dilation, as well as improved left ventricular function as compared to control diet animals. These effects were associated with enhanced reperfusion injury salvage kinases (RISK) pathway function in HFD hearts shown as increased Akt and GSK3β phosphorylation. These results demonstrate that dietary obesity without hyperglycemia or hypertension attenuates the impact of ischemia/reperfusion injury in association with increased insulin signaling and RISK activation. This study provides experimental support to the controversial concept of the obesity paradox in humans. Highlights: We examine a B6D2F1 mouse model fed with high fat diet during 6 months. Mice develop obesity with hyperinsulinemia and without hyperglycemia or hypertension. Obese mice show reduced ventricular post-infarction remodeling. Our results support the concept of the obesity paradox. Insulin dependent RISK activation is the mechanism proposed.